2022
DOI: 10.17221/42/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Use of metalaxyl against some soil plant pathogens of the class Peronosporomycetes - A review and two case studies

Abstract: Upon its discovery and implementation in plant protection, metalaxyl became one of the most important fungicides against Phytophthora infestans, but its efficiency has also been proven against other soil pathogens of the class Peronosporomycetes. The most important genus – Phytophthora comprises more than 150 plant pathogens, which cause significant losses in crop production or damage to natural plant associations. Many species of related genera Pythium, Phytopythium and Globisporangium have a similar ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 122 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Molinero-Ruiz et al (2008) reported a decrease on the effectiveness of two distinct active components (Metalaxyl and Metalaxyl-M) for controlling downy mildew in sunflowers is due to the ability of the novel strain to readily overcome P. halstedii resistance. Pánek et al (2022) indicated that the metalaxyl not limiting the pathogen penetration into a host plant but effectively reducing mycelial development. These findings are also consistent with our findings, which reveal that mefenoxam cannot restrict sporangia germination in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Molinero-Ruiz et al (2008) reported a decrease on the effectiveness of two distinct active components (Metalaxyl and Metalaxyl-M) for controlling downy mildew in sunflowers is due to the ability of the novel strain to readily overcome P. halstedii resistance. Pánek et al (2022) indicated that the metalaxyl not limiting the pathogen penetration into a host plant but effectively reducing mycelial development. These findings are also consistent with our findings, which reveal that mefenoxam cannot restrict sporangia germination in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The materials Tween 20, used as an aid dispersant to dissolve oil in water, and acetic acid as a solvent for chitosan, gave an inhibition rate of 20.5 and 32.2%, respectively. The fungicide's effectiveness may be due to the active substance Metalaxyl, as it works by its chemical effect to prevent and inhibit the synthesis of ribosomal RNA, as it does not prohibit the fungus from entering the plant tissues instead, it prevents the growth and reproduction of the fungus [16] or to the active substance Hymexazole, which has a role in inhibiting the biosynthesis of proteins and nucleic acids, or in the processes of oxidation and reduction, and thus in the energy production [17].…”
Section: Antagonistic Effect Of Rosemary Oil Against the Foxysporium ...mentioning
confidence: 99%
“…The resistance of P. cactorum against metalaxyl was first reported in 1988 by Utkhede and Gupta in an in vitro environment [ 25 ], while the resistance of P. cactorum isolates to mefenoxam in strawberry fields in the USA was reported for the first time by Jeffers et al in 2004 [ 26 ]. Recently, Marin and Peres [ 27 ] reported that the fungicides cymoxanil, fluopicolide, mandipropamid and oxathiapiprolin completely inhibited the mycelial growth of P. cactorum isolates from Florida at a concentration of 1 µg/mL, but significant differences in the resistance to some chemical fungicides have already been found between P. cactorum isolates or their genetic lineages [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%